Analisis Perbandingan Algoritma AES Dan RC4 Pada Enkripsi dan Dekripsi Data Teks Berbasis CrypTool 2 - Risa Naili Fitriana; Djuniadi Djuniadi (Systemic: Information System and Informatics Journal, 2021)
The development of technology is followed by a large amount of data. Not all of the data is presented to the general public, some data are strictly kept confidential because of certain interests. This study aims to test the encryption and decryption of text data (with *.txt format) to maintain confidentiality and compare the performance of the AES algorithm with RC4. This study uses the AES and RC4 algorithms with a key length of 256 bits using CrypTool 2 for encryption and decryption processes. The result of the first trial is that the encryption and decryption test of the AES algorithm on text data results in a different ciphertext size from the original text data. While the second trial was carried out by encryption and decryption of the RC4 algorithm on text data, resulting in the same ciphertext size before the simulation process was carried out. So from this research, the RC4 algorithm produces a smaller ciphertext size than using the AES algorithm.